Внутрішньомолекулярні водневі зв'язки у всіх можливих конформерах 2'-дезокситимідину: неемпіричний квантово-хімічний аналіз топології електронної густини - Жураківський, Р.О.; Говорун, Д.М. (Видавничий дім "Академперіодика" НАН України, 2007)
As many as 13 types of intramolecular hydrogen bonds are determined in 92 conformers of 2'-deoxythymidine nucleoside by means of quantum-chemical analysis (at DFT B3LYP/6–31G(d,p) theory level) of the electron density topology with Atoms-in-Molecules (AIM) theory. The total number of H-bonds is 171, and their types are C1'H…O2, C2'H2…O5', C2'H2…O2, C3'H…O2, C5'H1…O2, C5'H2…O2, C6H…O4', C6H…O5', C3'H…HC6, O5'H…HC6, O3'H…O5', O5'H…O3', and O5'H…O2. The conformational, geometric, and electron-topological properties of H-bonds are presented.